Socio-Technical Systems: Conceptual and Implementation Problems - Maton, Bob (Relations industrielles / Industrial Relations, 1988)
This paper explores possible reasons for the resistance by both workers and managers to introduction of the STS approach, despite its apparent benefits to both.